Fetal growth and cardio‐metabolic risk factors in the 20‐year‐old offspring. (19th August 2014) - Rytter, Dorte; Bech, Bodil H.; Frydenberg, Morten; Henriksen, Tine B.; Olsen, Sjurdur F.
Abstract Objective To investigate the association between prenatal growth patterns as estimated by biparietal diameter and cardio‐metabolic risk at 20 years. Design Follow‐up study. Setting Denmark 1988–2009. Population Two cohorts of children born between 1988 and 1990 (n = 707) and followed up in 2008–2009 (n = 333–509). Methods We have access to biparietal diameter from early ultrasound scan and birthweight. For each gender, biparietal diameter and birthweight, gestational age‐specific growth‐z‐scores were calculated. A change in growth trajectory was depicted as a shift in z‐score for the two growth measures. Multiple linear regression modeling was used to estimate associations between biparietal diameter and birthweight z‐scores and later cardio‐metabolic risk factors as well as estimating whether changing growth trajectory was associated with later cardio‐metabolic risk. Main outcome measures Self‐reported anthropometrics and clinically measured blood pressure, heart rate and biochemical measures associated with cardio‐metabolic health. Results After adjustments, biparietal diameter was not associated with any of the outcomes. Birthweight was positively associated with both adult height and weight and inversely associated with insulin, triglyceride and insulin resistance. Also, the data indicated a U‐shaped association between growth in the second half of pregnancy and adult body mass index among individuals with a low biparietal diameter in mid‐pregnancy. Conclusion Different patterns of intrauterine growth may be associated with later risk of cardio‐metabolic disease.